The Influence of Motivation and Competence on Air Traffic Controller Employee Performance Through Career Development at Perum Lppnpi's Approach Control Unit Jakarta - Suprapto Suprapto; Zonar Anjab Rabbani (Dinasti International Journal of Management Science, 2023)
This study aims to determine and analyze the direct and indirect effects of motivation and competency on em-ployee performance with career development as an intervening variable. The population of this study were all employees on duty at the Approach Control Unit (APP) of Perum LPPNPI Jakarta Branch, with a total sample of 132 ATC personnel. Retrieval of research data using a questionnaire instrument that has been tested on the instrument. The data analysis method in this study used the Structural Equation Model - Pertial Least Square (SEM-PLS). The results of this study suggest that motivation has a positive and significant direct effect on em-ployee performance. Competence has a positive and significant direct effect on employee performance. Motiva-tion has a positive and significant direct effect on career development. Motivation has a positive and signifi-cant effect on career development. Career development has no direct effect on employee performance. Also, motivation and competence have a positive and significant indirect effect on employee performance through career development.